Reputation, loneliness, satisfaction with life and aggressive behavior in adolescence - Musitu, Gonzalo; Buelga, Sofía; Murgui, Sergio; Pons, Javier (The Spanish Journal of Psychology, 2008)
The present study analyses the relationship between adolescents’ perception of reputation and aggressive behavior among peers. The sample is made up of 1319 adolescents aged 11 to 16 years old. Statistical analyses with structural equation modeling were carried out to examine the direct and indirect effect of perception of reputation (real and ideal) on aggressive behavior. Results indicate that adolescents’ real and ideal reputations are related both directly and indirectly to aggressive behavior. The indirect effects suggest that loneliness and life satisfaction mediate the relationship between adolescents’ reputation and their aggressive behavior. These findings and their implications are discussed.